A Greek battleground in southern Italy: new light on the ancient Sagra - Visonà, Paolo; Jansson, James R. (Journal of Greek Archaeology, 2017)
In the Battle of the Sagra River, the earliest known battle fought at a river in southern Italy, the army of Locri Epizephyrii (with the support of Rhegion) defeated superior forces of Kroton. This was one of the most salient events in the history of Magna Graecia before the fall of Sybaris in 510 BC. Its significance was magnified throughout the Greek world as an upset victory achieved through supernatural intervention: the Dioscuri were said to have come from Sparta to aid the Locrians. However, no primary sources about this conflict have survived and nothing is known about the topography of the battle.